Pierre Koffmann and Timothy Shaw: La Tante Claire - D., J.M. (Petits Propos Culinaires, 1992)
Pierre Koffmann and Timothy Shaw: La Tante Claire: Headline, London, 1992: 224 pp, colour photographs, index, £19.99.